2018
DOI: 10.1371/journal.pone.0202230
|View full text |Cite
|
Sign up to set email alerts
|

Continuous nicotine exposure does not affect resurgence of alcohol seeking in rats

Abstract: Alcohol is the most commonly used drug in the United States and alcohol abuse can lead to alcohol use disorder. Alcohol use disorder is a persistent condition and relapse rates following successful remission are high. Many factors have been associated with relapse for alcohol use disorder, but identification of these factors has not been well translated into preventative utility. One potentially important factor, concurrent nicotine use, has not been well investigated as a causal factor in relapse for alcohol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The procedure developed in Experiment 1 evaluated resurgence induced by loss of alternative reinforcement in Phase 3 under conditions where cocaine-seeking responses had no consequences. This is advantageous for making comparisons to other resurgence procedures (Frye et al, 2018;Nall et al, 2018Nall et al, , 2019Quick et al, 2011;Shahan et al, 2015) as well as other procedures that have examined relapse of previously punished drug seeking (Marchant, Khuc, Pickens, Bonci, & Shaham, 2013;Nall et al, 2019;Panlilio et al, 2003;Pelloux et al, 2018). However, humans are not likely to experience extinction of drug seeking following treatment with alternative reinforcement (Marchant, Li, et al, 2013;Panlilio et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure developed in Experiment 1 evaluated resurgence induced by loss of alternative reinforcement in Phase 3 under conditions where cocaine-seeking responses had no consequences. This is advantageous for making comparisons to other resurgence procedures (Frye et al, 2018;Nall et al, 2018Nall et al, , 2019Quick et al, 2011;Shahan et al, 2015) as well as other procedures that have examined relapse of previously punished drug seeking (Marchant, Khuc, Pickens, Bonci, & Shaham, 2013;Nall et al, 2019;Panlilio et al, 2003;Pelloux et al, 2018). However, humans are not likely to experience extinction of drug seeking following treatment with alternative reinforcement (Marchant, Li, et al, 2013;Panlilio et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Resurgence of drug seeking is often studied in animals using a three-phase procedure (Craig, Nall, Madden, & Shahan, 2016; Frye et al, 2018; Nall, Craig, Browning, & Shahan, 2018; Quick, Pyszczynski, Colston, & Shahan, 2011; Shahan, Craig, & Sweeney, 2015). In Phase 1, animals are trained to perform a target response to earn drug reinforcement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the large difference in active responding and reinforcers earned between cocaine and food options during self-administration, all subsequent analyses were performed on proportions of baseline responding (see Table 1 for raw responses and proportional transformations throughout the experiment). Proportions of baseline were calculated by dividing the response count on a given session by the mean of the response count from the last three sessions of self-administration (e.g., Frye et al, 2018). Thus, for each rat cocaine responses were normalized to cocaine responding during self-administration, and food responses were normalized to food responding during self-administration.…”
Section: Phase 2: Reinforcer Competitionmentioning
confidence: 99%
“…The resurgence effect suggests that there is potential for relapse when therapy concludes and incentives are withdrawn [14] which is known to occur [73]. Animal studies have shown that resurgence occurs when drugs such as alcohol or cocaine are used as reinforcers [74][75][76]. One potential point of contention is that Bouton and colleagues have conceptualised resurgence as renewal due to a novel context ('C') that is distinct from both the acquisition context ('A') and the extinction context ('B'), also known as ABC renewal [14].…”
Section: Resurgencementioning
confidence: 99%